Teacher Strategy in the Field of Islamic Religious Education Studies inInstill Values Character For Students at Al-Fauziah Private Madrasah Aliyah District. Mambi District. Mamasa - Hamzah, Muh; Lamabawa, Dahlan; Muchtar, M. Ilham (International Journal on Advanced Science, Education, and Religion, 2024)
This research aims to identify and analyze the strategies of teachers in the field of Islamic religious education in instilling character values ​​in Al-Fauziah Private Madrasah Aliyah students, Talippuki sub-district. Mambi District. Mamasa. The methodology of this research is descriptive qualitative with data collection techniques of observation, interviews and research instruments to collect information in order to reveal an empirical fact in an objectively scientific manner based on strong scientific logic in accordance with known scientific disciplines. The research results show that the students' character is basically good, but the influence of the external environment and also the lack of attention and support from their parents makes them experience obstacles in their enthusiasm for learning and school. So, to achieve school success, teachers in the learning process create strategies for appropriate learning methods and motivate students to stay in school until completion. In learning, teachers instill character values ​​that are instilled in students, namely the character of self-confidence, the character of discipline in learning, the character of enthusiasm for learning, the character of focus in learning, the character of being active in creativity.